2018
DOI: 10.1177/1558944718788687
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Reason for Readmission and Unscheduled Health Care Contact After Distal Radius Fracture

Abstract: For patients sustaining DRF, we report a 30-day readmission rate of 7% with 20% of patients having UHC. Patients with depression or anxiety were more likely to be both readmitted and have UHC. Identifying risk factors for readmission during initial presentation may help reduce readmissions. Improving pain relief strategies early may aid in decreasing the burden of UHC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 23 publications
(32 reference statements)
1
17
0
Order By: Relevance
“…Upon review of our institutional historical cohort, 22% of patients (n = 26 telephone calls, n = 20 urgent care/emergency department presentations, n = 4 both) either presented to the emergency department/ urgent care or made telephone calls to providers because of uncontrolled pain. These rates are consistent with Sumner et al, 68 which suggest a 20% rate of unscheduled health care contact. After perioperative pain management protocol implementation, we had no instances of unscheduled health care contact, which was a significant reduction compared with our historical group ( P = 0.016).…”
Section: Secondary Clinical Outcomessupporting
confidence: 91%
See 1 more Smart Citation
“…Upon review of our institutional historical cohort, 22% of patients (n = 26 telephone calls, n = 20 urgent care/emergency department presentations, n = 4 both) either presented to the emergency department/ urgent care or made telephone calls to providers because of uncontrolled pain. These rates are consistent with Sumner et al, 68 which suggest a 20% rate of unscheduled health care contact. After perioperative pain management protocol implementation, we had no instances of unscheduled health care contact, which was a significant reduction compared with our historical group ( P = 0.016).…”
Section: Secondary Clinical Outcomessupporting
confidence: 91%
“…Multiple large database reviews report readmission rates of 2% to 9% after DRF treatment. [67][68][69][70] However, these studies do not include other forms of unscheduled health care contact, such as telephone calls. Upon review of our institutional historical cohort, 22% of patients (n = 26 telephone calls, n = 20 urgent care/emergency department presentations, n = 4 both) either presented to the emergency department/ urgent care or made telephone calls to providers because of uncontrolled pain.…”
Section: Secondary Clinical Outcomesmentioning
confidence: 99%
“…This is consistent with previous studies that report rates of unplanned readmission after DRF ORIF to be between 0.9% and 8%. 12 , 17 , 24 Based on a multivariable analysis, predictors of readmission after DRF ORIF were identified to be ASA class > 3 (OR = 2.87), functionally dependent status (OR = 2.25), insulin-dependent diabetes (OR = 1.97), and remaining in hospital after the index surgery (inpatient procedure, OR = 2.04).…”
Section: Discussionmentioning
confidence: 99%
“…In a retrospective review of 353 patients who sustained DRF at a rural trauma center, Sumner et al found that patients with anxiety or depression were significantly more likely to be readmitted and to pursue unscheduled health care contact, including ED visits, than patients without those comorbidities (39 vs. 16%, p ¼ 0.01); however, they did not assess any type of preoperative intervention. 35 The study by Schwartz et al remains singular in the orthopaedic literature in the evaluation of psychotherapy visits as a preoperative intervention to modify outcomes for depression patients. 34 They found that the psychotherapy cohort had lower rates of health care utilization, including ED visits, 30-day and 90day readmissions, and prolonged lengths of stay, compared with their depression cohort without psychotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, studies have shown that the most common reasons for readmission or ED visits following treatment for DRF are related to pain, and that preoperative diagnoses of DDs are significantly correlated to increased pain intensity following hand surgery. [35][36][37][38][39] At the same time, studies have shown that patients with greater measures of resiliency and self-efficacy, as well as more realistic expectations of outcomes, are more capable of tolerating the pain associated with ORIF for DRF and other upper extremity surgeries. 9,14,40 As such, this is the proposed role of psychotherapy visits, depression screenings, or other nonpharmacologic interventions in targeting and strengthening these facets within patients prior to surgery for DRF, which may in turn lead to a tangible decrease in health care utilization among these patients.…”
Section: Discussionmentioning
confidence: 99%